2016
DOI: 10.1590/s1413-70542016000100010
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and bioactive compounds of adzuki beans cultivars using chemometric approach

Abstract: Azuki beans are small red grains rich in several essential nutrients used in traditional dishes in Asia that, nowadays present many applications around the world. This work aimed at evaluating angularis and niponensis cultivars from south region of Brazil. Both cultivars presented proximal composition similar to literature and the majority fatty acids were 18:2n-6, 16:0 and 18:3n-3. All samples showed polyunsatured fatty acids prevalence and nutritional indices and ratios considered adequate for biological sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
0
10
0
3
Order By: Relevance
“…No trabalho de Gohara et al (2016), as variedades de feijão azuki (Vigna angularis) cultivadas na cidade de Maringá, Paraná, apresentaram valores similares de composição química, com umidade de 13,07%, carboidratos de 62,26% e proteínas de 20,36%. Os feijões azuki deste estudo apresentaram baixo teor de lipídios (1,63%) e, no estudo de Gohara et al (2016), foram encontrados valores ainda menores de lipídios, ou seja, 0,45%. Durak et al (2013) também reportaram valores parecidos de proteínas (25,00%), carboidratos (55,00%) e lipídios totais (0,45%) nos feijões azuki vermelhos.…”
Section: Análises Físico-químicas Dos Feijões Azukiunclassified
See 2 more Smart Citations
“…No trabalho de Gohara et al (2016), as variedades de feijão azuki (Vigna angularis) cultivadas na cidade de Maringá, Paraná, apresentaram valores similares de composição química, com umidade de 13,07%, carboidratos de 62,26% e proteínas de 20,36%. Os feijões azuki deste estudo apresentaram baixo teor de lipídios (1,63%) e, no estudo de Gohara et al (2016), foram encontrados valores ainda menores de lipídios, ou seja, 0,45%. Durak et al (2013) também reportaram valores parecidos de proteínas (25,00%), carboidratos (55,00%) e lipídios totais (0,45%) nos feijões azuki vermelhos.…”
Section: Análises Físico-químicas Dos Feijões Azukiunclassified
“…Esse alimento apresenta elevado teor de proteína vegetal e carboidratos, destacando-se pelo alto teor de fibras alimentares, vitaminas e minerais, além de possuir baixa quantidade de lipídios (KLOMKLAO et al, 2010;MUKAI;SATO, 2011). No Brasil, o feijão azuki ainda é pouco consumido, mas se adaptou bem às condições climáticas, sendo cultivado, na maioria das vezes, pelos descendentes dos imigrantes japoneses (GUARESCHI et al, 2013;GOHARA et al, 2016).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…It has been reported that adzuki contains health-promoting antioxidants, such as flavonoids and tocopherols [ 1 , 2 , 3 ], and that the flavonoids are transferred to the rice when cooked with rice [ 4 ]. Recently, we have reported that a diethyl ether-extract of the adzuki bean can suppress starch digestion of the homogenates of cooked non-glutinous rice and that taxifolin, quercetin, and a purplish pigment vignacyanidin (a cyanidin-catechin conjugate) in the extract can contribute to the suppression [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adzuki bean (Vigna angularis) is a legume, commonly used as traditional food (manju youkan, wagashi,and amanatto) in China and Japan (Gohara et al, 2016). Adzuki beans are known to be a rich source of protein, carbohydrates, minerals, vitamins, and fiber (Tjahjadi, Lin, & Breene, 1988).…”
mentioning
confidence: 99%